The study of multisensory interception for interaction with objects and others in visually impaired children - Bartolini, Tommaso; Riberto, Martina; Vitali, Helene; Wallace, Mark T.; Gori, Monica (Frontiers in Human Neuroscience, 2025)
Interception refers to goal-directed motor actions aimed at interacting with moving objects and is essential for both motor co-ordination and social engagement. In childhood, interceptive skills support environmental exploration, peer interaction, and participation in play and sports. For children with visual impairments, the lack of visual cues compromises the development of these skills, potentially limiting motor competence and opportunities for social interaction. Despite its clinical and developmental relevance, research on interception in visually impaired (VI) children is extremely limited. This mini review synthesizes findings from studies on interceptive skills in VI adults, as well as in sighted and VI children. We discuss how vision contributes to interceptive actions, and how alternative sensory pathways can compensate in its absence. We highlight major limitations of current literature, including poor ecological validity, a lack of longitudinal data, and scarce attention to multisensory and social aspects. To address these gaps, we propose future research directions that include cross-sectional and longitudinal studies, multisensory paradigms, and the use of virtual reality technologies to simulate naturalistic environments. These approaches may inform inclusive and rehabilitative interventions that support the motor and social development of VI children through accessible, engaging, and developmentally appropriate interceptive experiences.